1934
DOI: 10.1002/jmor.1050560108
|View full text |Cite
|
Sign up to set email alerts
|

The material continuity and individuality of the somatic chromosomes of Ambystoma tigrinum, with special reference to the nucleolus as a chromosomal component

Abstract: Two features of this study have furnished direct evidence for the material continuity and individuality of the chromosomes in the epithelial cells of the larvae of Ambystoma tigrinum (1) the tracing of the complete history of a specific chromosome, the nucleolus‐containing chromosome, throughout the successive stages of mitosis and interkinesis, (2) the following of the exact parallelism in behavior (during mitosis) of the chromosomes in a given nuclear group with that in a single chromosome which has been iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1938
1938
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…Early tetrad mapping studies located d in the distal region of an unknown chromosome (Lindsley et al 1955;Armstrong 1984) and several studies have observed an association between segregation of white and segregation of NOR variants (reviewed by Sinclair et al 1978). The NOR is located subterminally on one of the four largest chromosomes (Paramenter 1919;Dearing 1934;Haschuka and Brunst 1965;Callan 1966;Cuny and Malacinski 1985). In our study we identified a single region of the genome that was significantly associated with white.…”
Section: Segregation Of Molecular Markerssupporting
confidence: 55%
“…Early tetrad mapping studies located d in the distal region of an unknown chromosome (Lindsley et al 1955;Armstrong 1984) and several studies have observed an association between segregation of white and segregation of NOR variants (reviewed by Sinclair et al 1978). The NOR is located subterminally on one of the four largest chromosomes (Paramenter 1919;Dearing 1934;Haschuka and Brunst 1965;Callan 1966;Cuny and Malacinski 1985). In our study we identified a single region of the genome that was significantly associated with white.…”
Section: Segregation Of Molecular Markerssupporting
confidence: 55%
“…In 1954, Gall described a region on one of the lampbrush chromosomes from oocytes of Ambystoma tigrinurn, to which nucleoli were attached. The position of this region corresponded with that of a prominent subterminal constriction which is associated with the formation of nulceoli at mitotic telophase in this species (Dearing, 1934).…”
Section: The 'Lampbrush' Nucleolar Organizermentioning
confidence: 52%
“…2, 3, 4, 6, and 7; Figs. [28][29][30][31][32][33][34][35][36][37][38]. The anaphase and the second division proceed normally.…”
Section: Torsten Wickbommentioning
confidence: 99%